HUBUNGAN KEMAMPUAN AWAL, PENERAPAN METODE KERJA KELOMPOK DENGAN HASIL BELAJAR SISWA KELAS III SD - Mandasari, Devi; Sabri, Tahmid; Halidjah, Siti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to determine the relationship between initial ability and the application of group work methods with student learning outcomes in learning citizenship education class III LKIA Pontianak Selatan Elementary School. The subjects of this study were third grade students of South Pontianak LKIA Elementary School in 2019/2020 school year. The object of this study is the initial ability, group work methods, and student learning outcomes. In this research the method chosen is descriptive method, with a form of interrelation study (interrelative study). This is because this study intends to describe the relationship of the independent variable or variable X, namely the initial ability and group work with the dependent variable or variable Y, namely learning outcomes. This study examined the population of all grade III students of South Pontianak LKIA Elementary School, which totaled 21 students. Data obtained through the students' initial abilities, the application of group work methods, and the student's final results. Data analysis techniques in this study used hypothesis testing (product moment correlation). The results showed that at an error rate of 5%, the magnitude of the correlation between initial ability, group work methods, and student learning outcomes (r count) was 0.974 with a rtable of 0.413. Because rcount> rtable it can be concluded that there is a positive relationship between initial abilities, group work methods, and student learning outcomes.Â Keywords : Relationships, Initial Skills, Group Work Methods, Learning Outcomes, and Citizenship Education